Impacts of a Gamification Application for Teaching Software Measurement: An Experience Report - Furtado, Lennon Sales; Oliveira, Sandro Ronaldo Bezerra (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
This paper presents a gamification approach, using games elements and serious game, with a focus on teaching the software measurement process. This approach aims to encourage classroom interaction and thus promote interest in the process. The proposal was applied in two classes with a total of 22 students from a Federal University in Brazil. As a result, one of the case studies yielded 80% of the evaluations with positive criteria for the class using gamification. Finally, gamification has had a positive effect for those involved when it is not just about using game elements in a non-playful context. In conclusion, the proposal helped in the software measurement teaching process by creating a competitive and collaborative environment, focusing on classroom interactions.